The Application of Creative Design in Apparel Industry - Tian, Bingqiang; Hu, Shouzhong (Scientific Research Publishing, 2016)
The article explained and analyzed the creative design of clothing from concept to the main manifestations and characteristics, and the relationship between apparel feature type and creative design of clothing was discussed. It presented ideas that creative design of clothing reflect in variety of clothing types mainly in three forms: subversion, innovation-based and functional innovation. Creative design of clothing is the fundamental of development of Chinese fashion. It should be done to reform education and train creative design fashion talent.
Keywords: Creative Design of Clothing; Originality; Style of Expression